A comparative study of genotoxicity endpoints for women exposed to different levels of indoor radon concentrations. (2nd January 2022) - Dicu, Tiberius; Virag, Piroska; Brie, Ioana; Perde-Schrepler, Maria; Fischer-Fodor, Eva; Victor, Bogdan; Cucoș, Alexandra; Burghele, Bety-Denissa
Abstract: Background and purpose: Radon and its radioactive progenies are the most important source of ionizing radiation of natural origin, being classified as a Group 1 carcinogen. The aim of this study is to investigate the genotoxic effects of a wide range of indoor radon concentrations, as well as the kinetics of the process of repairing DNA-induced lesions by a challenging dose of gamma irradiation. Material and methods: Female subjects residing in the Băiţa-Ştei radon priority area were selected as the exposed group. The reference group was comprised of women from the same county (Bihor), but located in an area with an average indoor radon concentration typical of the county from which they were taken. Radon concentration values of 300 Bq/m 3 and 148 Bq/m 3, respectively, were chosen as a threshold in order to capture the impact of radon exposure between the groups. The alkaline comet assay was used in order to measure the DNA damage, as well as the repair kinetics at 2 and 24 h after 2 Gy challenging doses of gamma irradiation using peripheral blood lymphocytes. From the serum of the subjects, the oxidative damage by 8-hydroxydeoxyguanosine as well as the PARP induction was evaluated. The chromosomal aberrations were evaluated using the Cytokinesis Block MicroNucleus Assay. Results: A statistically significant increase was observed in terms of DNA-induced lesions assessed by comet assay for the exposed group compared to the reference group. A positive correlation was obtained between DNA damage and the annual effective dose, respectively with the radon progenies concentrations. A statistically significant difference was also observed for the frequency of the micronuclei between the exposed – reference groups. Significantly faster repair kinetics of DNA-induced lesions was recorded for the first 2 h after gamma irradiation in the reference group compared to the exposed group. Using the threshold of 300 Bq/m 3 for radon concentration, faster kinetics of DNA damage repair for people exposed to low radon concentrations, compared to those exposed to higher concentrations for the second phase of DNA repair kinetics was observed. Conclusion: An increased radiosensitivity of lymphocytes, as well as slower repair kinetics, may be associated with exposure to higher indoor radon concentrations.